2013
DOI: 10.1016/j.juro.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Premature Ejaculation Results in Female Sexual Distress: Standardization and Validation of a New Diagnostic Tool for Sexual Distress

Abstract: The Female Sexual Distress Scale-Revised-Premature Ejaculation questionnaire fulfills psychometric requirements for measuring sexual distress related to partner sexual dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…In addition to the anatomical-physiological characterisation of orgasmic pleasure, the quality of the couple's relationship (Limoncin et al, 2013) is considered to be a fundamental factor and seems to be related to the perception of orgasm. Unfortunately, this aspect has been somewhat neglected, especially regarding premature ejaculation (PE).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the anatomical-physiological characterisation of orgasmic pleasure, the quality of the couple's relationship (Limoncin et al, 2013) is considered to be a fundamental factor and seems to be related to the perception of orgasm. Unfortunately, this aspect has been somewhat neglected, especially regarding premature ejaculation (PE).…”
Section: Introductionmentioning
confidence: 99%
“…Those who are affected by PE often appear to be discouraged by the unsatisfying duration of intercourse, as well as by the sense of inadequacy related to their inability to satisfy their partner, it has negative consequences on the Quality of Life (QoL) of patients and their partners. A recent study conducted by Limoncin et al (22) showed that women with a partner affected by PE were more likely than controls to experience significant sexual distress. Until 2008 the pharmacological treatment of PE was based on off-label use of SSRIs; in 2009 the European Agency for the Evaluation of Medicinal Products (EMA) approved the use of Dapoxetine for the specific treatment of PE in patients aged between 18 and 64 years.…”
Section: Discussionmentioning
confidence: 98%
“…Similar findings have been reported for PE, a largely recognized partner-oriented male sexual symptom. Indeed, female partners of patients with PE are more likely to suffer from sexual problems and dissatisfaction than partners of non-PE men (Byers & Grenier, 2003;Hartmann et al, 2005;Hobbs et al, 2008;Graziottin & Althof, 2011;Limoncin et al, 2013). Interestingly, a previous study evaluating the associations between intimacy, quality of life, and sexual dysfunction in men, demonstrated that all aspects of intimacy were lower in men reporting PE than in men not reporting PE (McCabe, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally assumed that ED (Conaglen et al, 2010) and PE (Limoncin et al, 2013) are distressing diseases, not only for men who experience the conditions but also for their female partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation